The Problems in Professional Competence of Teachers in Teaching English Subjects at Vocational High Schools - -, SYAMSINAR -; Jabu, Baso (ELT WORLDWIDE, 2015)
Â  Â  Â  Â  Â  Â This research was intended to investigate the problems in professional competence faced by the English teachers of vocational high schools in Gowa, South Sulawesi. This research applied descriptive qualitative method.Â  The data were collected by using three instruments namely questionnaire, interview and observation checklist. The participants were two experienced English teachers, two inexperienced English teachers, and eight students. The professional competence indicators adapted from the Regulation of the Minister of National Education of the Republic of Indonesia No. 16/2007. The research found that there were eleven problems faced by the teacher in relation to their professional competence. In English teachersâ competence especially in linguistic aspect, the major problem faced by the teachers is dealing with lacking of the vocabulary for special terms. In addition, the research also indicated that there were two other serious problems faced by the teachers. First, they faced problem in developing the teacher professionalism continuously. Second, they do not use information and communication for communicating maximally.Keywords: Â Â  professional competence, experienced English teachers, inexperiencedÂ Â Â  English teacherÂ